EFEKTIVITAS PENERAPAN MEDIA POWER POINT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Erinata, Danu; Noor, Agus Sastrawan; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to know the effectiveness of the application of power-point learning media. This research was conducted using pre-experimental design with the one-group pretest-posttest design. The subject of this study was 8th-grade students of MTs Hidayatul Muslimin 2 Kubu Raya. The techniques of data collection are direct observation technique, direct communication technique, and measurement technique. The tools of data collecting in this research were notebook, interviews and learning outcomes tests in the form of pretest and posttest, the results of the normality test state that the results of residual values are normally distributed with a significant value of 0.544 > 0.05. While the results of the hypothesis test state that Ho is rejected and Ha is accepted based on the sig value. (2-tailed) at the value of the pretest and posttest with a value of 0,000 which means smaller than 0.05. It shows that there are significant differences after the application of the power-point learning media. The pretest average value is 53,29 and the posttest average value is 80.79. So, with the application of power-point learning media seen an increase in student learning outcomes subject in the 8th grade of MTs Hidayatul Muslimin 2 Kubu Raya and shows the effect size criteria are very effective at 1.99.Keywords: IPS Subjects, Learning Outcomes, Power Point Learning MediaPENDAHULUANPerkembangan yang terus terjadi di ilmu pengetahuan